Pengungkapan Manajemen Laba Terhadap Pengungkapan Corporate Social Responsibility (Csr Disclosure) Dengan Mekanisme Gcg Sebagai Variabel Moderasi Pada Perusahaan Perkebunan Kelapa Sawit Yang Terdaftar Di Bursa Efek Indonesia - Ayang Pratama (Fakultas Ekonomi Prodi Akuntansi, 2023)
Abstract The purpose of this journal is to find out how the role of GCG Mechanism in moderating Earning Management influencing CSR Disclosure of the Sub-Group of Oil Palm Plantation Companies listed on the Indonesia Stock Exchange period 2017 until 2021. The research method used is analytical descriptive, which Moderating Regression Analysis is used in answering research hypothesis. The results showed that Earning Management influence CSR Disclosure, the total of Audit Committee can moderating Earning Management influence CSR Disclosure but Proportion of Board of Commissioner can not moderating Earning Management influence CSR Disclosure. Keywords: Earning Management, GCG Mechanism, Corporate Social Responsibility, Palm Oil Industry